If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -3 = -27 Reorder the terms: -3 + x = -27 Solving -3 + x = -27 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + x = -27 + 3 Combine like terms: -3 + 3 = 0 0 + x = -27 + 3 x = -27 + 3 Combine like terms: -27 + 3 = -24 x = -24 Simplifying x = -24
| 9p-7p+4p-6p= | | 3x/4=9/2 | | 9y^2+54y+0=0 | | 9x+8=4x-3 | | -3=-27 | | -2(2x-4)+8x-4= | | -12=-3/4z | | 17q-14xq=11q | | 3x(t-3)=27 | | x/-11=5 | | F=9/5x+32 | | 9x-(2x-1)=37 | | 36/(2x)=6 | | 5+x=-22 | | 5(7b-6)=110 | | -2(5s-6)-12=-2(9s+4)-3 | | 36/2x=6 | | -1.3+2.7=.2y | | -13x+22=37 | | 7/3a=14 | | y=-9x+44 | | 3x(12-3)=27 | | 6x+19=8x+7 | | -2(5x-6)-12=-2(9s+4)-3 | | b+b2+b/6=190 | | 4*x^3+5*x^2+x=1 | | -10m-4=4-10m | | (4+8x)/(2x+1) | | 180=6000*.12*t | | 4(5x-1)-4=14x-2 | | 5(3x+1)=2(5x-4)+6x | | 27(1.4+1.2)-26(1.4+1.2)= |